Study on Customers’ Perception of Mobile Banking - Kamatchi, T. Devi; Jayanthi, V. (International Journal of Psychosocial Rehabilitation, 2020)
In the global age, with the ever developing technology advancements, mobile banking has made the customers easier to access their accounts, even from rural/remote areas. With technology as a driving force, the commercial bank, now-a-days improves their current mobile banking services which results in high satisfaction among the customers. Mobile banking has a revolutionary impact on the scope of business and various transactions carried out daily. Mobile banking introduces the use of smart phones to operate online banking transactions such as account checking, transfer of money,payment of bills andrecharge of mobile. Mobile banking is available 24/7 to customers for financial transactions. Mobile banking services offered by banks helps to have increased number of satisfied customers